1998
DOI: 10.1128/mcb.18.7.4245
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Gene Encoding Hepatocyte Nuclear Factor 3γ Results in Reduced Transcription of Hepatocyte-Specific Genes

Abstract: The winged helix transcription factor hepatocyte nuclear factor 3␥ (HNF3␥) is expressed in embryonic endoderm and its derivatives liver, pancreas, stomach, and intestine, as well as in testis and ovary. We have generated mice carrying an Hnf3g-lacZ fusion which deletes most of the HNF3␥ coding sequence as well as 5.5 kb of 3 flanking region. Mice homozygous for the mutation are fertile, develop normally, and show no morphological defects. The mild phenotype change of the Hnf3g ؊/؊ mice can be explained in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 35 publications
1
121
0
3
Order By: Relevance
“…This is due either to functional redundancy between individual FoxA and GATA factor proteins or an essential role for some of these factors prior to the onset of hepatic development. [61][62][63][64][65][66][67][68][69][70] For example, development of Gata6 Ϫ/Ϫ mouse embryos is blocked before hepatic specification due to an indispensable requirement for GATA6 in extraembryonic endoderm differentiation. 63,65 This early embryonic lethality has, however, recently been circumvented by providing Gata6 Ϫ/Ϫ embryos with a wild-type extra-embryonic endoderm via tetraploid embryo complementation.…”
Section: From Where Do Hepatic Cells Arise?mentioning
confidence: 99%
See 1 more Smart Citation
“…This is due either to functional redundancy between individual FoxA and GATA factor proteins or an essential role for some of these factors prior to the onset of hepatic development. [61][62][63][64][65][66][67][68][69][70] For example, development of Gata6 Ϫ/Ϫ mouse embryos is blocked before hepatic specification due to an indispensable requirement for GATA6 in extraembryonic endoderm differentiation. 63,65 This early embryonic lethality has, however, recently been circumvented by providing Gata6 Ϫ/Ϫ embryos with a wild-type extra-embryonic endoderm via tetraploid embryo complementation.…”
Section: From Where Do Hepatic Cells Arise?mentioning
confidence: 99%
“…73,81,128,129 These include the hepatocyte nuclear factors HNF1␣ and ␤, c/EBP␣, HNF4␣, and FoxA, which act in combination to control aspects of hepatocyte differentiation and liver function. 67,73,[130][131][132][133][134][135][136][137][138] Of these transcriptional regulators, the nuclear hormone receptor HNF4␣ appears to be particularly potent in controlling hepatocyte differentiation. 133,134,139 Hnf4 knockout embryos die before the onset of liver development due to a crucial role for this factor in regulating extra-embryonic endoderm function.…”
Section: What Governs the Establishment Of Hepatic Architecture And Mmentioning
confidence: 99%
“…These include HNF-1␣ and -␤ (vHNF-1), c/EBP family, HNF-3␣, -␤ and -␥, HNF-4␣, and more recently HNF-6 (Cereghini, 1996; Lemaigre et al, 1996;Samadani and Costa, 1996). Gene-disruption studies in mice have revealed that many of these transcription factors have crucial roles in regulating liver function and metabolism in adult or newborn mice (Wang et al, 1995;Pontoglio et al, 1996;Croniger et al, 1997;Tanaka et al, 1997;Kaestner et al, 1998;Lee et al, 1998;Kaestner et al, 1999;Shih et al, 1999). Somewhat surprisingly, however, liver development is relatively unaffected in the majority of these mutant mouse strains.…”
Section: Hnf-4␣ Is Required For Complete Differentiation Of Hepatocytesmentioning
confidence: 99%
“…They are also inactivated by insulin, similar to Foxa2 [13,20]. Increased longevity has been reported in Caenorhabditis elegans that are deficient for insulin signaling cascades and mice with white-adiposetissue-specific ablation of the insulin receptor [19]. Caloric restriction also causes similar increased longevity through Sir2/SIRT1-mediated deacetylation and the subsequent activation of the Foxo transcription factors, inducing genes involved in cell growth arrest and anti-oxidative stress (Figure 1) [20].…”
Section: Updatementioning
confidence: 83%
“…Foxa1 is a potent transactivator mediating glucagon gene expression [16,17], whereas Foxa3 regulates glucose homeostasis during a prolonged fast through the maintenance of hepatic Glut2 and gluconeogenic gene expression [18,19].…”
Section: Updatementioning
confidence: 99%